Tumor-Associated Macrophages in Pancreatic Ductal Adenocarcinoma: Origin, Polarization, Function, and Reprogramming - Yang, Sen; Liu, Qiaofei; Liao, Quan (Frontiers in Cell and Developmental Biology, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is a highly lethal malignancy. PDAC is only cured by surgical resection in early-stage but remains a relatively high possibility of recurrence. The development of PDAC is closely associated with the tumor microenvironment. Tumor-associated macrophages (TAMs) are one of the most abundant immune cell populations in the pancreatic tumor stroma. TAMs are inclined to M2 deviation in the tumor microenvironment, which promotes and supports tumor behaviors, including tumorigenesis, immune escape, metastasis, and chemotherapy resistance. Here, we comprehensively reviewed the latest researches on the origin, polarization, function, and reprogramming of TAMs in PDAC.